Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1046/j.0028-646x.2001.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization patterns in a mycorrhiza‐defective mutant tomato vary with different arbuscular‐mycorrhizal fungi

Abstract: Summary• Interactions between a mycorrhiza-defective tomato ( Lycopersicon esculentum ) mutant, rmc , and different species of arbuscular mycorrhizal (AM) fungi were investigated and compared with those with the wild-type cv. 76R.• Both cv. 76R and rmc were challenged with Glomus intraradices , G. mosseae , G. coronatum, G. versiforme , G. etunicatum , G. fasciculatum , Gigaspora margarita and Scutellospora calospora using a nurse pot inoculation system.• Cv. 76R demonstrated normal colonization patterns for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 32 publications
(104 reference statements)
3
63
0
Order By: Relevance
“…AM association has been shown to induce modifications in root system architecture and in root morphogenesis (Berta et al 1990;Schellenbaum et al 1991;Bouma et al 2001). The effects seem to be dependent on fungus and plant species, as well as on environmental conditions (Smith and Read 1997;Bouma et al 2001;Gao et al 2001). Root architecture of carob seedlings seemed to be more responsive to nutrient levels than to AM association.…”
Section: Discussionmentioning
confidence: 99%
“…AM association has been shown to induce modifications in root system architecture and in root morphogenesis (Berta et al 1990;Schellenbaum et al 1991;Bouma et al 2001). The effects seem to be dependent on fungus and plant species, as well as on environmental conditions (Smith and Read 1997;Bouma et al 2001;Gao et al 2001). Root architecture of carob seedlings seemed to be more responsive to nutrient levels than to AM association.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of Gao (2002) Colonisation in the inoculated nurse plants (A. porrum) was relatively high at both harvests, indicating that inoculum potential in the nurse pots was not likely to have influenced relative colonisation of rmc by the two fungi. Previous work has shown that A. porrum nurse plants with colonisation between 40 and 90% are capable of initiating extensive colonisation of the wild-type progenitor of rmc (Cavagnaro et al, 2001a;Gao et al, 2001). The differential colonisation of A. porrum by G. sp.…”
Section: Colonisationmentioning
confidence: 97%
“…The inoculum was derived from pot cultures of Glomus coronatum Giovannetti (WUM 16) or Glomus sp. WFVAM 23 (referred to as G. versiforme (Karsten) Berch in Gao et al ., 2001;Cavagnaro et al ., 2001a) raised on leek ( Allium porrum L . cv.…”
Section: Soil Fungi and Plantsmentioning
confidence: 99%
See 2 more Smart Citations